Financial crime spillovers: Does one gain to be avenged? - Laure de Batz (Charles University in Prague, Institute of Economic Studies (IES), 2019)
This paper examines the spillovers of the sanction procedures on listed companies which were victims of others' financial regulatory breaches (i.e. regulated entities or individuals). Market manipulators can be investigated and possibly sanctioned for doing so, according to the French enforcement scheme. This research enriches past literature with a new complementary perspectivebon victims. Past work typically focused on abnormal returns primarily for investigated and/or sanctioned listed companies, as well as for plaintive firms, in a wide range of jurisdictions. The results demonstrate that victim firms suffer, on average, significant negative abnormal returns after the sanction. Naming victims hence may possibly be synonym of double punishment, as the firms already suffered during the violation period. It demonstrates a market failure where victims are not properly differentiated from wrongdoers. This article investigates the information content of such market behavior. The markets also incorporate the information content of the decision and of the parties at stake. All in all, those results plead for an anonymization of victims over the enforcement process, to protect from being sanctioned, and possibly suggest to name and shame market manipulators.
Keywords: G14; G18; K42; N24; 330; Sanction; victim; financial markets; event study; regulation; fraud; information and market efficiency; listed companies